44 Lifespan of negative experiences in functional neurological disorder patients. (28th May 2019) - Mehmood, Aneesa; Levita, Liat; Reuber, Markus; Mayberry, Emily
Abstract : Aims: Exploration of the relationship between negative life experiences and patients with Functional Neurological Disorder (FND), by analysing patient and non-clinical group responses to a new questionnaire called the Lifespan of Negative Experiences Scale (LiNES). LiNES was designed to examine predisposing vulnerabilities and perpetuating factors in individuals with FND by retrospectively assessing experiences of interpersonal trauma, affect and relationship insecurity at three developmental stages – childhood, adolescence and adulthood. Methods: LiNES, CATS (measure of childhood abuse and trauma), RSQ (measure of relationship insecurity) and PANAS (measure of affect) questionnaires were administrated to 71 individuals with FND. Analyses were conducted to assess the reliability of the LiNES, explore correlations between different psychological domains within the FND group and to test whether LiNES scores predicted FND group membership. In addition, FND patients' responses where compared to 270 matched healthy controls. Results: The LiNES subscales had high internal consistency and correlated with CATS, RSQ and PANAS. Levels of interpersonal trauma were higher in FND patients than controls during childhood, adolescence and adulthood. High levels of negative affect were found in FND patients in adulthood compared to controls but no significant differences were found between FND patients and controls in relationship insecurity at any developmental stage. On the RSQ, FND patients had higher anxious and avoidant relationship styles. LiNES trauma scores at each developmental stage predicted FND status with over 80% accuracy. Additionally, FND patients self-reported more symptoms (SDQ-20) and a higher prevalence of comorbid conditions compared to controls. Conclusions: The LiNES is a new brief retrospective measure of negative life experiences. Although psychological factors may not be necessary to the diagnosis of FND, they are substantially more common in FND patients compared to controls. In particular, a history of interpersonal trauma seems to play an important role in those with FND. These factors therefore are likely to play a pathophysiological role in many patients and their recognition is important for treatment. This study provides new insights into the association between the timing of negative experiences and the subsequent effect on an individual. Furthermore, the results support the use of LiNES as a valid screening tool in the clinical setting in patients presenting with functional symptoms with diagnostic and therapeutic implications.